Holocene Growth History and Evolution of the Scott Reef Carbonate Platform and Coral Reef - Collins, Lindsay; Testa, Viviane; Zhao, J.; Qu, D. (Royal Society of Western Australia, 2011)
As a prominent isolated oceanic atoll-like reef within the Oceanic Shoals Biozone to the west of the Kimberley coast, Scott reef is a small carbonate platform located in a distal ramp setting on Australia's Northwest Shelf. Rising from depths of 400-700 m it is a complex of two large isolated coral reefs separated by a deep channel; the pear-shaped North Reef and the crescent-shaped South Reef. Small differences in subsidence rates indicate differential subsidence between the paired platforms. Holocene (MIS 1, last 10ka) reef initiation was at 11.3 ka, soon after Meltwater Pulse 1B thereby bracketing the Holocene growth phase to the subsequent deglaciation sea-level rise. The crest of southeast North Reef (and the rising sea-level) reached close to present sea level (-1.5m LAT) by 2.7 ka ago. There is no record of the southwest Australian sea level high stand of about +2m some 7 ka BP. The Holocene reef growth history record obtained for this long lived and resilient reef system is one of the most detailed yet for the western margin of Australia.